La filosofia morale e il futuro - Boella, Laura (Filosofia Morale/Moral Philosophy, 2022)
If we ask ourselves about the future of moral philosophy, I would say that its first task today is to think about the future, to take the future as the horizon of theoretical work and of contribution to the public debate. The future is a scabrous, discredited theme, which collects the rubble of classical utopias, of faith in progress, of the broken promises of the Western enlightenment and rationalist vision (democracy, equality, human rights).The future confronts us with the essence of the moral problem, i.e. the need to rethink the relationship that today seems to be a clear separation between the individual, his capacity for initiative (agency), his vulnerability (not being a master, but rather guest in one’s own home) and living together with others in its many manifestations.